Manufacturing transformation comparative studies of industrial development in Africa and emerging Asia - Newman, Carol 1977-; Page, John M. 1949-; Rand, John 1974-; Shimeles, Abebe; Söderbom, Måns; Tarp, Finn 1951- (Oxford University Press, 2016)
While it is possible for economies to grow based on abundant land or natural resources, more often structural change-the shift of resources from low-productivity to high-productivity sectors-is the key driver of economic growth. Structural transformation is vital for Africa. The region's much-lauded growth turnaround since 1995 has been the result of making fewer economic policy mistakes, robust commodity prices, and new discoveries of natural resources. At the same time, Africa's economic structure has changed very little. Primary commodities and natural resources still account for the bulk of the region's exports. Industry is most often the leading driver of structural transformation. Africa's experience with industrialization over the past thirty years has been disappointing. In 2010, sub-Saharan Africa's average share of manufacturing value added in GDP was ten per cent, unchanged from the 1970s. Actually, the share of medium- and high-tech goods in manufacturing production has been falling since the mid-1990s. Per capita manufactured exports are less than ten per cent of the developing country average. Consequently, Africa's industrial transformation has yet to take place
Includes bibliographical references and index
Keywords: Manufacturing industries; Entwicklungsländer; Manufacturing industries -- Developing countries; Manufacturing industries -- Africa; Manufacturing industries -- Asia; Industrialization -- Africa; Entwicklung; Wirtschaftswachstum; Wirtschaftliche Integration; Africa; Asia; Developing countries; Afrika; Asien